Impact of seed priming and foliar nutrition on horse gram and pearl millet as an alternate for maize in hydroponic cultivation - Hemalatha, M; Joseph, M; Manikkavasakam, E; Vinitha, N; Kumar, G (Plant Science Today, 2025)
Soil-based agriculture faces challenges from various human activities like deforestation, urbanization and industrialization. In response, scientists have introduced hydroponic cultivation, a soil-less farming method completed within 7-8 days in a nutrient-rich aqueous medium. To address this shift, an experiment was conducted at V.O.C. Agricultural College and Research Institute, Killikulam, between February and April 2022 during summer. Using a factorial completely randomized design (FCRD) with 15 treatments and three replications, to study the effects of seed priming and foliar nutrition on the growth, yield and quality of horse gram and pearl millet as best alternative for regular maize under hydroponics. Seed priming treatments including hydro-priming, 2 % humic acid priming and 1 % moringa leaf extract priming, while foliar nutrition treatments included control, 0.1 % humic acid, 20 % vermiwash, 1 % Azophos and 1 % 19:19:19 WSF (Water Soluble Fertilizer) applied at 5 days after sowing (DAS). Results indicate that combining effect of seed priming with 2 % humic acid and foliar nutrition of humic acid @ 0.1 % significantly influenced growth parameters, the higher green fodder yield of 11 and 13.7 kg m-2, water use efficiency, superior proximate fodder quality viz., crude protein (29.5 and 15.4 %), crude fibre (15.5 and 11.8 %), crude fat (2.9 and 4.32 %), total ash (3.26 and 2.49 %) and NFE (Nitrogen Free Extract) (48.83 and 66.9 %). Ultimately, combining seed priming with 2 % humic acid and foliar nutrition with 0.1 % humic acid emerged as the most effective strategy for promoting growth, yield and superior fodder quality of horse gram and pearl millet as the best alternate to regular maize.